Scintimetric assessment of synovitis activity during treatment with disease modifying antirheumatic drugs. Issue 12 (December 1988) - Olsen, N; Halberg, P; Halskov, O; Bentzon, M W
Abstract : In a double blind trial of 36 patients with rheumatoid arthritis a new scintimetric method was applied to three comparable patient groups before and after eight months' treatment with levamisole, penicillamine, or azathioprine. Technetium-99m pyrophosphate scintigraphy of both hands was performed on a gammacamera with a computer attached, immediately after the administration of the tracer. The uptake ratio of each proximal interphalangeal (PIP) joint and the mid-half of the adjacent proximal phalanx was calculated from the activity counted for one minute. A scintimetric index was expressed as the sum of eight uptake ratios. This index was higher for each of the three patient groups before start of treatment than that for 10 age matched controls. After eight months of treatment the index, the number of PIP joints with clinical signs of synovitis, and the total circumference of the PIP joints decreased in the penicillamine and azathioprine groups. The scintimetric method reliably reflected local synovitis activity and its changes but, like grip strength and PIP circumference, was not a representative measure of the overall activity of the disease.